2020
DOI: 10.4236/ce.2020.118098
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Highly Immersive Programme towards Language Proficiency of Primary School Pupils: A Literature Review

Abstract: Being proficient in using English language is very crucial, especially in Malaysia context as the language has been considered as a second language status. However, primary school pupils still have problems in language proficiency especially in learning English. The implementation of Highly Immersive Programme in Malaysia education system is one of the steps taken by the Ministry of Education to solve the poor language proficiency problem among the primary school pupils by involving and immersing pupils in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The research revealed that immersion-based learning technology could have a positive impact on ESL teaching. Abdullah and Mohamad (2020) researched the implementation of a highly immersive curriculum on primary school students’ language ability and argued that it encouraged students to learn English in an effective English environment. Meanwhile, the research found that students welcomed experiential learning opportunities to explore foreign cultures and languages outside the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…The research revealed that immersion-based learning technology could have a positive impact on ESL teaching. Abdullah and Mohamad (2020) researched the implementation of a highly immersive curriculum on primary school students’ language ability and argued that it encouraged students to learn English in an effective English environment. Meanwhile, the research found that students welcomed experiential learning opportunities to explore foreign cultures and languages outside the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…However, the proficiency level in the English language among Malaysian students was reported to be low (Soh & Sharif, 2021). The implementation of programs such as the Highly Immersive Programme (HIP) aimed to enhance the language proficiency of primary school pupils (Abdullah & Mohamad, 2020). Additionally, the use of English as a medium of instruction in higher education institutions was widespread (Soh & Sharif, 2021).…”
Section: English Language Learning (Ell) In Malaysiamentioning
confidence: 99%